Design of a Water Heater Heating System Based on Industrial Control Configuration Software WinCC - Yu, Sicheng (International Journal of Mechanical and Electrical Engineering, 2024)
The report presents the design and implementation of a water heater control system utilizing SIMATIC WinCC configuration software. The research highlights the transition from traditional manual control methods to automated systems, demonstrating significant improvements in efficiency, user convenience, and energy conservation. By leveraging the advanced capabilities of WinCC, the system effectively monitors and controls water levels and temperatures, integrating real-time data processing with a user-friendly interface. The project showcases enhanced operational efficiency, safety, and environmental sustainability, emphasizing the critical role of technological advancements in industrial automation.